2014
DOI: 10.1021/ja506194z
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Protonation of Side Chain Aminoethylene Repeats in N-Substituted Polyaspartamides Promotes mRNA Transfection

Abstract: Fine-tuning of chemical structures of polycation-based carriers (polyplexes) is an attractive strategy for safe and efficient mRNA transfaction. Here, mRNA polyplexes comprising N-substituted polyaspartamides with varied numbers of side chain aminoethylene repeats were constructed, and their transfection ability against human hepatoma cells was examined. Transfection efficacy clearly correlated with the number of aminoethylene repeats: polyplexes with odd number repeats (PA-Os) produced sustained increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 21 publications
2
114
0
Order By: Relevance
“…Studies have shown correlations of knockdown/transfection efficiencies of therapeutic RNA polyplexes with modulations of polymer properties. 1416 However, there is lack of molecular level understanding of polyplex structure and dynamics and how these properties vary as a function of key vector properties such as molecular weight, hydrophobicity, and charge density. 17 Polyplexes are often difficult to characterize in terms of molecular stoichiometry, thermodynamic constants, exchange kinetics, and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown correlations of knockdown/transfection efficiencies of therapeutic RNA polyplexes with modulations of polymer properties. 1416 However, there is lack of molecular level understanding of polyplex structure and dynamics and how these properties vary as a function of key vector properties such as molecular weight, hydrophobicity, and charge density. 17 Polyplexes are often difficult to characterize in terms of molecular stoichiometry, thermodynamic constants, exchange kinetics, and dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…To date, naked, chemically modified, or protamine-complexed mRNA have shown promise in phase I/II cancer trials (24)(25)(26). Recently, preclinical development of materials specific for mRNA delivery has resulted in cationic polymers such as polymethacrylates (27)(28)(29), poly(aspartamides) (30,31), and polypeptides (32), as well as multicomponent cationic lipid or lipid-like formulations (21,(33)(34)(35)(36). In many of these examples, however, transfection efficiencies can be quite low, ranging 20-80% in cells (18), with likely much lower efficiencies in vivo, which requires either high mRNA doses or hydrodynamic injections (32,37).…”
mentioning
confidence: 99%
“…This phenomenon, along with a potentiometric titration, has been utilized to predict the protonation structures of N1 (EDA), N2 (DET), N3 (TET) and N4 (TEP) at pH 7.4, with N2 (DET) and N4 (TEP) bearing two and three protonation structures in equilibrium, respectively (Scheme 1). 2526 Using the same approach, we found that N5 (PEH) assumes a ~56% degree of protonation at pH 7.4. This implies that nearly three out of five amine groups on the side chain are protonated.…”
Section: Resultsmentioning
confidence: 87%